ANALISIS RASIO KEUANGAN YANG MEMPENGARUHI RETURN ON INVESTMENT PADA PERUSAHAAN TELEKOMUNIKASI YANG GO PUBLIC DI BURSA EFEK INDONESIA (BEI) - Pertiwi_13, icha (MOTIVASI, 2021)
The purpose of this research is to know the significant influence of the Current Ratio partially on the Return On Investment of telecommunication companies listed on the Indonesia Stock Exchange, the significant influence of Debt Equity Ratio partially on the Return On Investment of telecommunication companies listed on the Indonesia Stock Exchange partially influences working capital turnover on the Return On Investment of telecommunication companies listed on the Indonesia Stock Exchange , the significant influence of Net Profit Margin partially on the Return On Investment of telecommunication companies listed on the Indonesia Stock Exchange and the significant influence of Current Ratio, Debt Equity Ratio, Working Capital Turnover, Net Profit Margin simultaneously on Return On Investment of telecommunication service companies listed on the Indonesia Stock Exchange